2014
DOI: 10.4274/tjo.13471
|View full text |Cite
|
Sign up to set email alerts
|

Glokom Hastalığı ve Yaşa Bağlı Makula Dejeneransının Yaşam Kalitesi Üzerine Etkileri

Abstract: Amaç: Glokom hastalığı ve yaşa bağlı makula dejeneransı (YBMD) nedeniyle tedavi gören hastalarda, depresif belirtilerin ve anksiyete belirtilerinin varlığının ve yaşam kalitesinin değerlendirilmesidir. Gereç ve Yöntem: 1 Mart 2008-30 Haziran 2008 tarihleri arasında, kliniğimizde takip ve tedavisi yapılan 60 glokom ve 60 YBMD hastası çalışmaya alındı. Kontrol grubu olarak, gözlük muayenesi için gelen ve ek bir şikayeti olmayan 60 hasta dahil edildi. Glokom ve YBMD hastalarının psikiyatrik belirtiler ve yaşam ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…19 In a controlled study conducted on patients with glaucoma and AMD, Kocak et al showed that the percentage of depression was significantly higher among the patients with glaucoma or AMD than among the controls. 20 However, the difference between the patients with glaucoma and those with AMD was not significant.…”
Section: Discussionmentioning
confidence: 90%
“…19 In a controlled study conducted on patients with glaucoma and AMD, Kocak et al showed that the percentage of depression was significantly higher among the patients with glaucoma or AMD than among the controls. 20 However, the difference between the patients with glaucoma and those with AMD was not significant.…”
Section: Discussionmentioning
confidence: 90%